Clinical profile and outcome of pelvi-ureteric junction obstruction (PUJO) in children presenting above 1 year - S., Pramod; Ramji, Ashwath Narayan (International Surgery Journal, 2018)
Background: Pelvi-ureteric junction obstruction (PUJO) is defined as anatomical or functional obstruction to the flow of urine from the pelvis to the upper ureter. With the advent of ultrasonography most of the cases of PUJO are identified in antenatal period. The treatment protocol for antenatal diagnosed PUJO is standardized. Few children present later in life. Present study was done to evaluate clinical profile and outcome of children presenting with PUJO above 1 year. Methods: A retrospective observational study conducted by the department of Paediatric Surgery, KIMS hospital Bangalore. All children with PUJO above 1 year of age from January 2015 to January 2018 were included. Clinical, biochemical and imaging findings of these children were tabulated. A diuretic renogram was done to confirm the diagnosis. The children underwent either pyeloplasty or nephrectomy, depending on the function of the kidney. In children with calculi, pyelolithotomy with pyeloplasty was done. The children were followed up post-surgery. Results: Twenty-six children were included in the study. Mean age of presentation was 6.86±4.13years. Most common presentation was pain abdomen. Left kidney was commonly involved. The mean anteroposterior pelvic dimension (APPD) of involved kidney was 38.96±17.7 mm. 5 children presented with poorly functioning kidney with split renal function less than 10%. In three children PUJO was associated with pelvic calculi. Out of the 26 children simple nephrectomy was required in 4 (15%) children. The remaining 22 children underwent pyeloplasty. Mean duration of stay was 6.19±1.8 days. Post-pyeloplasty diuretic renogram showed improved drainage with improved function. Conclusions: PUJO is common cause of urinary obstruction in children. Delay in diagnosis or presentation leads to increased chances of renal damage and loss. Hence it is important to diagnose PUJ obstruction at the earliest and receive prompt treatment.